Marxist Intellectuals and the Working-Class Mentality in Germany, 1887-1912 - Eley, Geoff (Labour / Le Travail, 1995)
The article reviews the book, "Marxist Intellectuals and the Working-Class Mentality in Germany, 1887-1912," by Stanley Pierson.
Keywords: BOOKS -- Reviews; MARXIST Intellectuals & the Working-Class Mentality in Germany 1887-1912 (Book); Nonfiction; PIERSON, Stanley; Social conflict